Ant biodiversity and its environmental predictors in the North Kimberley region of Australia’s seasonal tropics - Cross, A.; Myers, C.; Mitchell, C.; Cross, S.; Jackson, C.; Waina, R.; Mucina, L.; Dixon, Kingsley; Andersen, A. (Springer, 2016)
Northern Australia supports the world’s largest estate of undeveloped tropical savannas, but previous studies of ant diversity in the region have covered only a fraction of its land area and habitat diversity. We assess patterns of ant species and functional diversity, their environmental predictors, and biogeographic significance in the central North Kimberley region of Australia’s seasonal tropics. Pitfall traps were used to sample ants at 69 plots in representative savanna habitats, collecting a total of 158 species from 30 genera. Total richness was estimated to be as high as 237 species. At least 29 species across 12 genera appear to have been collected for the first time. Only a single invasive ant was recorded from the study area. Based on cluster analysis we identified six compositionally distinct ant communities, each associated with a combination of vegetation type and underlying geology. Species richness and functional diversity was highest in savanna woodlands and grasslands on sandstone-derived soils, with increasing richness also predicted by a lower mean daily temperature range, a more complex understorey, and lower precipitation seasonality. The abundance of nearly all commonly trapped species was related to temperature, moisture, and habitat variables, although these relationships were highly idiosyncratic. Nearly 40 % of the collected species are known only from the North Kimberley region. The high level of endemism, together with the lack of introduced ant species, identifies the North Kimberley ant fauna as having outstanding biodiversity value. Our identification of ant community types based on mappable soil and vegetation units provides a basis for predicting ant distribution throughout the broader region, and therefore contributing to regional conservation planning and management.